The provision of Primary Health Care in two rural districts of the Eastern Cape Province with particular reference to human resources and accessibility - Part 2: The results and recommendations - M. Thipanyana; T.R. Mavundla (AOSIS, 1998)
Part 1 of this article dealt with the introduction, problem statement and the research methods. This article details the results and the recommendations with the aim of improving the provision of primary health care in rural districts of the Eastern Cape Province. This article is dealt with in three phases: phase I gives the results of interviews of community people, phase II deals with the results of the questionnaire administered to professional nurses and phase III entails the recommendations.